Aumento da produtividade: utilizando a metodologia Six Sigma e Lógica Fuzzy, um estudo de caso em uma empresa do Pólo Industrial de Manaus – PIM - FERREIRA, Marcela Seixas (Universidade Federal do Pará, 2012)
This study uses six sigma methodology in order to increase the productivity of the Line of LCD (Liquid Crystal Display) in a factory in the Pólo Industrial de Manaus - PIM and a fuzzy inference system to measure the increase of productivity, where we identified several parameters based on the six sigma methodology. Among which, according to the degree of relevance of specialists in this study, we can highlight: waste, production capacity and time study. Emphasizing further that the proposed system is of great importance to practitioners and researchers of production management, who want results that reduce costs and therefore increase profits of the organization.